(untitled) (International journal of artificial intelligence, 2026)
This article examines the historical and contemporary place of the Western Azerbaijan issue in Azerbaijan’s diplomacy. Against the backdrop of deportations in 1905, 1918–1920, 1948–1953, and 1987–1991, the violation of the rights of Azerbaijanis from Western Azerbaijan and the destruction of their cultural heritage are analyzed. Since the 2000s, the issue has increasingly entered diplomatic discourse and international legal frameworks. Through presidential speeches, the "Return Concept", diaspora initiatives, and information diplomacy, the Western Azerbaijan issue has been brought to international attention. The article also evaluates the problem's relevance to regional security and geopolitical dynamics, offering future-oriented recommendations.